CNPY3’s regulation of tumor microenvironment and its impact on colon cancer aggressiveness - Xucan Gao; Biaohuan Zhou; Xiudong Feng; Zhouxin Ji; Qiang Li; Huining Liu (Molecular Medicine)
Abstract Background Canopy FGF signaling regulator 3 (CNPY3) has been implicated in tumor progression. However, its specific role in colon cancer (CC) remains unclear. This study aims to investigate the function of CNPY3 in CC and its potential as a therapeutic target. Methods A total of 201 CC tissue specimens and 67 adjacent non-cancerous tissues were collected for analysis. CNPY3 expression was assessed using immunohistochemistry and quantitative real-time PCR. Functional assays were conducted in CC cell lines (HT-29 and SW-620) following CNPY3 knockdown to evaluate its effects on cell proliferation, migration, and apoptosis. Gene expression profiling, fibroblast co-culture experiments, and in vivo xenograft models were also conducted. Results Increased CNPY3 expression correlated with advanced tumor stages and poorer prognosis. Knockdown of CNPY3 significantly inhibited cell proliferation, migration, and induced apoptosis in CC cell lines. CNPY3 depletion also modulated fibroblast behavior, inhibiting their transformation into cancer-associated fibroblasts. Pathway analysis revealed that CNPY3 knockdown affected the cell cycle and p53 signaling pathways, and reduced activation of the MAPK and PI3K/AKT pathways. Additionally, CNPY3 knockdown enhanced CC cell sensitivity to 5-fluorouracil. In vivo studies demonstrated that CNPY3 knockdown resulted in smaller tumor sizes and weights than controls. Conclusions CNPY3 is a crucial regulator in CC progression, correlating with tumor aggressiveness and poor patient outcomes. Targeting CNPY3 may offer a promising therapeutic strategy and a valuable prognostic marker in CC management.